2014
DOI: 10.32674/jis.v4i2.474
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Help-Seeking Intentions Among International and African American College Students: An Application of the Theory of Planned Behavior

Abstract: This study examined the relationship between social-cognitive factors (e.g., attitudes, subjective norms, and perceived behavioral control), psychological distress, and help-seeking intentions for a sample of 111 international and African American college students. The results of this study showed that the Theory of Planned Behavior (TPB) variables (e.g., attitudes, subjective norms, and perceived behavioral control) accounted for 17.7 % of the variance in help-seeking intentions. The first hypothesis, which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 26 publications
6
39
1
1
Order By: Relevance
“…There were 15 studies conducted in the US, three studies in India, two in Nigeria, one in Ghana, one in Taiwan, one in Saudi Arabia, one in Lebanon, one in Pakistan, one in the United Arab Emirates, one in Oman and one in Canada. The studies in the US focused on healthcare-seeking behaviours related to general and mental health; perceived stigma related to seeking healthcare; expenditures associated with healthcare; the association between medical mistrust and the use of health services; the use of online tools to seek healthcare; and the staffing for and scope of services offered in student health centres (Basch et al, 2018;Burlaka et al, 2014;Davies et al, 2000;Dennis and Hicks, 2006;Eisenberg et al, 2009;Fortuna et al, 2009;Gavgani et al, 2013;Han and Pong, 2015;Lau et al, 2014;McBride et al, 2013;Mesidor and Sly, 2014;Nicoteri and Arnold, 2005;Price et al, 2013;Turner and Keller;Zhang, 2013). Similarly, the studies in India, Nigeria, Lebanon, Canada, Oman, Pakistan, Taiwan and Ghana focused on general healthcare-seeking behaviours among college students and the use of online tools in seeking healthcare (Afolabi et al, 2013;Ahmad et al, 2017;Ajaegbu and Ubochi, 2016;El Kahi et al, 2012;Kuuire et al, 2015;Luo et al, 2018;Menon et al, 2017;Moazzam et al, 2018;Osei Asibey, et al, 2017;Sultan et al, 2017;Vaz et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 15 studies conducted in the US, three studies in India, two in Nigeria, one in Ghana, one in Taiwan, one in Saudi Arabia, one in Lebanon, one in Pakistan, one in the United Arab Emirates, one in Oman and one in Canada. The studies in the US focused on healthcare-seeking behaviours related to general and mental health; perceived stigma related to seeking healthcare; expenditures associated with healthcare; the association between medical mistrust and the use of health services; the use of online tools to seek healthcare; and the staffing for and scope of services offered in student health centres (Basch et al, 2018;Burlaka et al, 2014;Davies et al, 2000;Dennis and Hicks, 2006;Eisenberg et al, 2009;Fortuna et al, 2009;Gavgani et al, 2013;Han and Pong, 2015;Lau et al, 2014;McBride et al, 2013;Mesidor and Sly, 2014;Nicoteri and Arnold, 2005;Price et al, 2013;Turner and Keller;Zhang, 2013). Similarly, the studies in India, Nigeria, Lebanon, Canada, Oman, Pakistan, Taiwan and Ghana focused on general healthcare-seeking behaviours among college students and the use of online tools in seeking healthcare (Afolabi et al, 2013;Ahmad et al, 2017;Ajaegbu and Ubochi, 2016;El Kahi et al, 2012;Kuuire et al, 2015;Luo et al, 2018;Menon et al, 2017;Moazzam et al, 2018;Osei Asibey, et al, 2017;Sultan et al, 2017;Vaz et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Three articles detailed the effect of studying in a health-related discipline on healthcare-seeking behaviours (Al-Asraj et al, 2013;Sawalha et al, 2017;Vaz et al, 2012). Five articles discussed healthcare-seeking behaviours related to mental healthcare (Burlaka et al, 2014;El Kahi et al, 2012;Menon et al, 2017;Mesidor and Sly, 2014). Table 1 provides a summary of each article related to healthcare-seeking behaviour among college students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Konstruk dasar dari sikap dapat ditelusuri melalui teori planned behavior yang dikemukakan oleh Ajzen pada tahun 1991 (Mesidor & Sly, 2014). Sikap terhadap perilaku didefinisikan sebagai evaluasi individu atas perilaku tertentu, disertai keyakinan bahwa perilaku tersebut akan menuai hasil positif atau negatif.…”
Section: Sikap Terhadap Pencarian Bantuan Psikologisunclassified
“…Willis-O'Connor (2014) identified factors that contribute to the underutilization of campus-based counseling services by international students, with culture highlighted as one of the key factors in help-seeking behavior. Mesidor and Sly (2014) reported that 17.7% of variance in help-seeking intentions for international and African American students was accounted for by socialcognitive factors, such as attitudes, subjective norms, perceived behavioral control, and psychological distress. Shea and Yeh (2008) investigated the impact of adherence to Asian values and the stigma often associated with receiving psychological help by Asian American college and graduate students.…”
Section: Help-seeking Behaviorsmentioning
confidence: 99%